Pembelajaran Menulis Teks Drama Menggunakan Metode Picture and Picture - anita pratiwi arif; Teti Sobari; Elly Syarifah Aeni (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Learning to write drama texts basically reaps many problems including the difficulties of students in learning to write. Many of them find it difficult to start the writing process, developing words into sentences correctly, of course, are considered as difficult and tedious things in determining the theme and story line in the drama script. This research was conducted at SMAN 1 Cipatat which is located in Ciptaharja Village, West Bandung Regency. The formulation of the problem in this study is the difficulty of students in writing drama scripts. This study aims to answer the formulation of problems related to the difficulty of learning to write drama texts in students. Learning to write drama texts using the picture and picture method is expected to provide new innovations in learning and education. This research method uses descriptive qualitative and uses data collection techniques in the form of writing skills tests. Based on the results of research conducted on class XI students during the learning process of writing drama texts on the initial test getting an average score of 68.7 and the final test getting an average score of 78.2 which is included in the good category.Keywords: Learning, Writing Drama Text, Picture and Picture